Radiotherapy for Hodgkin lymphoma - Specht, Lena; Yahalom, Joachim (Springer, 2011)
This book deals in detail with all aspects of the best practice in modern radiotherapy for Hodgkin lymphoma. It provides the background and rationale for the inclusion of radiotherapy in today's combined-modality approach, including special clinical situations such as Hodgkin lymphoma in children, in the pregnant patient, and in the elderly. Radiotherapy planning using state-of-the-art imaging, target definition, planning software, and treatment equipment is expounded in detail. Acute and long-term side effects of radiotherapy are analyzed, and the implications for modern radiotherapy approach.